2022
DOI: 10.3389/fimmu.2022.841445
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Traps Increase Burden of Bleeding by Damaging Endothelial Cell in Acute Promyelocytic Leukaemia

Abstract: The rate of complete remission of acute promyelocytic leukemia (APL) is currently over 90% because of the use of all-trans retinoic acid (ATRA) with arsenic trioxide (ATO). However, hemorrhagic mortality has emerged as the most significant barrier to APL-induced remission. Neutrophils extracellular traps (NETs/ETs) cause vascular leakage by damaging the integrity of endothelial cells. We have previously demonstrated that APL cells treated with ATRA/ATO undergo a cell death process, releasing extracellular chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
0
11
1
Order By: Relevance
“…Targeting extracellular traps production may be an effective strategy to alleviate vascular leakage and reduce the incidence of bleeding in APL. [ 58 ] Chemokines are chemotactic cytokines that regulate cell migration, positioning and interaction. The chemokine axes are crucial in the leukemia microenvironment and are also involved in the migration and extravasation of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting extracellular traps production may be an effective strategy to alleviate vascular leakage and reduce the incidence of bleeding in APL. [ 58 ] Chemokines are chemotactic cytokines that regulate cell migration, positioning and interaction. The chemokine axes are crucial in the leukemia microenvironment and are also involved in the migration and extravasation of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…78 NETs also impact the endothelium and thereby on the thrombotic risk through induction of endothelial cell activation and induction of tissue factor, 79 as well as inducing endothelial cell damage or vascular leakage. 80,81 Hence NET interference could also reduce thrombotic risk through less endothelial cell activation and reduction of vascular leakage.…”
Section: Nets and Aberrant Immunothrombosis Trigger Atherothrombotic ...mentioning
confidence: 99%
“…Accumulating evidence suggests that the TME can induce NET formation in various types of cancer, including hematologic malignancy ( 72 74 ) and solid tumors, such as breast cancer ( 75 ), ovarian cancer ( 76 ), gastric cancer ( 77 ), hepatic carcinoma ( 78 ), lung cancer ( 79 ), and colon cancer ( 80 , 81 ). In particular, studies have revealed that NETs are increased in the peripheral blood and tumor tissues of patients with cancer ( 16 , 76 , 82 ).…”
Section: Evidence Of Nets Promoting Tumor Progressionmentioning
confidence: 99%